Winter Pea: Promising New Crop for Washington's Dryland Wheat-Fallow Region - Schillinger, William F. (Frontiers in Ecology and Evolution, 2017)
A 2-year tillage-based winter wheat (Triticum aestivum L.)-summer fallow (WW-SF) rotation has been practiced by the vast majority of famers in the low-precipitation (< 300 mm annual) rainfed cropping region of east-central Washington and north-central Oregon for 140 years. Until recently, alternative crops (i.e., those other than WW) so far tested have not been as economically viable or stable as WW-SF. A 6-year field study was conducted near Ritzville, WA (292 mm avg. annual precipitation) to determine the yield and rotation benefits of winter pea (Pisum sativum L.) (WP). Two 3-year rotations were evaluated: WP-spring wheat (SW)-SF versus WW-SW-SF. Winter pea yields averaged 2443 kg/ha versus 4878 kg/ha for WW. No fertilizer was applied to WP whereas 56 kg N and 11 kg S/ha were applied to WW. Winter pea used significantly less soil water than WW. Over the winter months, a lesser percentage of precipitation was stored in the soil following WP compared to WW because: (i) very little WP residue remained on the soil surface after harvest compared to WW, and (ii) the drier the soil, the more precipitation is stored in the soil over winter. However, soil water content in the spring was still greater following WP versus WW. Soil residual N in the spring (7 months after the harvest of WP and WW) was greater in WP plots despite not applying fertilizer to produce WP. Spring wheat grown after both WP and WW received the identical quantity of N, P, and S fertilizer each year. Average yield of SW was 2298 and 2011 kg/ha following WP and WW, respectively (P< 0.01). Adjusted gross economic returns for these two rotation systems were similar. Based partially on the results of this study, numerous farmers in the dry WW-SF region have shown keen interest in WP and acreage planted WP in east-central Washington has grown exponentially since 2013. This paper provides the first report of the potential for WP in the typical WW-SF region of the inland Pacific Northwest (PNW).